Cloud cuckoo land - Doerr, Anthony, 1973- (New York : Scribner, 2021)
"The heroes of Cloud Cuckoo Land are children trying to figure out the world around them, and to survive. In the besieged city of Constantinople in 1453, in a public library in Lakeport, Idaho, today, and on a spaceship bound for a distant exoplanet decades from now, an ancient text provides solace and the most profound human connection to characters in peril." --
Keywords: Space -- Fiction; Libraries -- Fiction; Historical fiction; Science fiction